Environmental sustainability and capital investment appraisal. (1st January 2002) - McDermott, Tom; Stainer, Alan; Stainer, Lorice
Capital investment appraisal and its associated techniques are discussed in relation to the environment and its sustainability. Economic feasibility is to be linked to health, safety and comfort as well as conservation, preservation and regeneration. Environmental policies must be integrated with capital investment decisions; this is because conventional investment appraisal procedures are often unsuitable for the green agenda to sustain nature. Moreover, contemporary strategic decision makers are becoming increasingly aware of their economic as well as their social responsibilities by having to confront the dual business objectives of being competitive and ethical. Methods are provided to incorporate more relevantly the environmental challenges into capital project decisions, focusing upon quality of life outcomes.